Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapters 1-5 Cumulative Review Problem Set - Page 233: 14



Work Step by Step

We will evaluate the expression by first simplifying the expression and then substituting $x=-2$ into the resultant expression: $-2(x-4)+3(2x-1)-(3x-2)$ =$-2x+8+6x-3-3x+2$ =$-2x+6x-3x+8-3+2$ =$(-2x+6x-3x)+(8-3+2)$ =$(x)+(7)$ =$-2+7$ =$5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.